2010
DOI: 10.1021/jf102669p
|View full text |Cite
|
Sign up to set email alerts
|

The Flavonol Isorhamnetin Exhibits Cytotoxic Effects on Human Colon Cancer Cells

Abstract: The aim of this study was to determine whether isorhamnetin, an immediate 3'-O-methylated metabolite of quercetin, affects proliferation, cell death, and the cell cycle of human colon carcinoma (HCT-116) cells. Isorhamnetin was found to be a potent antiproliferative agent in a dose- and time-dependent manner, with an IC50 of 72 μM after 48 h of incubation as estimated by MTT assay. Flow cytometry and fluorescence microscopy analysis showed that isorhamnetin exerted a stimulatory effect on apoptosis and necrosi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
75
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 102 publications
(82 citation statements)
references
References 32 publications
6
75
0
1
Order By: Relevance
“…Ramachandran 22 found that Iso inhibited the migratory/invasive properties of gastric cancer cells through modulation of the PPAR-γ activation pathway. Jaramillo 23 found that Isoinhibtied colon cancer cells growth by interrupting cell cycle progression. Iso is also found to promote lung cancer cell apoptosis through mitochondriadependent caspase activation in vitro and vivo 24 .…”
Section: +mentioning
confidence: 99%
“…Ramachandran 22 found that Iso inhibited the migratory/invasive properties of gastric cancer cells through modulation of the PPAR-γ activation pathway. Jaramillo 23 found that Isoinhibtied colon cancer cells growth by interrupting cell cycle progression. Iso is also found to promote lung cancer cell apoptosis through mitochondriadependent caspase activation in vitro and vivo 24 .…”
Section: +mentioning
confidence: 99%
“…1,22 LoVo cells (1 · 10 6 ) were seeded in 6sixwell flat-bottomed plates, grown overnight until they reached 80% confluence, and then treated with vehicle alone (0.1% DMSO) or with PNSE (0, 100, or 500 lg/mL) for 48 h. After treatment, the detached cells in the medium were collected and combined with the remaining adherent cells that were detached by brief trypsinization (0.25% trypsin-EDTA, Sigma-Aldrich). Cell pellets were fixed in 70% ethanol, washed in PBS, resuspended in 1.0 mL of PBS containing 1.0 mg/mL RNase and 50 lg/mL PI, incubated in the dark for 30 min at room temperature, and analyzed with a GUAVA Ò easyCyteÔ 8HT flow cytometer (Millipore).…”
Section: Cell Cycle Analysis Using Flow Cytometrymentioning
confidence: 99%
“…1,16,17 DMSO was used as the vehicle to deliver PNSE, and the final concentration of DMSO in all experiments was 0.1%. All experiments were done independently in triplicate per experimental point.…”
Section: Cell Culturementioning
confidence: 99%
See 2 more Smart Citations